3000mpa grade ultra-high strength steel wire and method for manufacturing the same
Patent Information
- Application Number
- CN202611193011.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-08-07
AI Technical Summary
传统生产方法中,冷拉拔形变量直接决定了钢丝强度的上升的多少,但是受限于初始盘条的晶粒尺寸;同时,高强度钢丝的成品前热处理也可使钢丝强度有限上升,但是很难突破2500 MPa
[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
Smart Images

Figure CN122686915B_ABST
Abstract
Description
Technical Field
[0001] This invention pertains to steel wire and its manufacturing method, specifically a 3000MPa grade ultra-high strength steel wire and its preparation method. Background Technology
[0002] Ultra-high strength steel wire is a key material supporting modern engineering structures. It possesses advantages such as high strength, good wear resistance, and suitable toughness and ductility, making it a high-performance metal wire suitable for use under high stress conditions. It is mainly used in galvanized steel wire for long-span bridge cables, automotive tire cord wire, and cutting diamond wire for photovoltaic applications. Traditional high-strength, high-carbon steel wire rods are mainly produced through austenitization and isothermal transformation to obtain typical sorbitic beaded rods, achieving both high strength and a certain degree of drawability. The process involves surface treatment of heat-treated high-carbon steel rods followed by multiple continuous cold drawing, high-strength steel wire, pre-finished heat treatment, and coating.
[0003] In the preparation of high-carbon steel wire, steel wires with strength and dimensions meeting application requirements are generally obtained through cold drawing deformation. Due to work hardening, the strength of the steel wire increases continuously with the increase of the cold drawing deformation. In traditional production methods, the cold drawing deformation directly determines the extent of the increase in steel wire strength, but it is limited by the grain size of the initial wire rod. At the same time, heat treatment before finishing high-strength steel wire can also increase the strength of the steel wire to a limited extent, but it is difficult to exceed 2500 MPa.
[0004] Traditional processes for producing 3 GPa grade steel wire primarily rely on heavy cold drawing of high-carbon pearlitic steel (true strain ε > 3), which not only leads to a surge in production costs but also typically limits the diameter of the finished wire to the micrometer level. While martensitic steel possesses extremely high initial dislocation density, it is highly susceptible to early brittle fracture during cold drawing due to insufficient plasticity reserves. Existing tempering martensitic processes often aim to obtain spherical carbides, improving toughness but sacrificing strain strengthening potential. How to induce nanoscale evolution of the martensitic matrix under lower strain conditions to obtain steel wires with both millimeter-scale diameters and ultra-high strength is a pressing technical bottleneck in the field of high-performance metal products. Summary of the Invention
[0005] Purpose of the invention: In order to overcome the shortcomings of the existing technology, the purpose of this invention is to provide a simple, convenient and efficient method for preparing 3000MPa grade ultra-high strength steel wire. Another purpose of this invention is to provide a 3000MPa grade ultra-high strength steel wire that combines high strength and high plasticity.
[0006] Technical solution: The present invention provides a method for preparing 3000MPa grade ultra-high strength steel wire, comprising the following steps:
[0007] Step 1: Heat the medium-high carbon low alloy wire rod to austenitize it, and then quench it to obtain quenched martensitic wire rod.
[0008] Step 2: Temper at 400~450℃ to obtain wire rods with tempered martensite structure;
[0009] Step 3: Remove the oxide film from the wire rod with tempered martensite structure and perform phosphating lubrication protection treatment;
[0010] Step 4: Perform multiple immersion water tank drawing processes on the material obtained in Step 3, controlling the true strain of cold drawing ε≥1.90, to obtain tempered martensitic steel wire.
[0011] Step 5: Hold the material obtained in Step 4 at 300~400℃ for 10~20 minutes, then immediately cool it with water mist to obtain 3000MPa grade ultra-high strength steel wire.
[0012] Furthermore, in step one, the medium-high carbon low alloy wire rod includes the following elements by mass percentage: C: 0.6~0.8 wt%, Mn: 0.5~1.0 wt%, Si: 0.5~1.5 wt%, Cr: 0.3~0.6 wt%, with the balance being Fe.
[0013] Furthermore, in step one, the heating temperature is 850~860 ℃, and the temperature is maintained for 8~15 min.
[0014] Furthermore, in step two, the tempering time is 20~60 s.
[0015] Furthermore, in step two, plate-like carbides with a spacing of approximately 30-35 nm precipitate from the wire rods with tempered martensite structure.
[0016] Furthermore, in step three, the oxide film is removed by acid washing or mechanical methods.
[0017] Furthermore, in step three, the phosphating lubrication protection treatment involves immersing the wire rod with tempered martensitic structure in a zinc-based or manganese-based phosphating solution at 80-90°C before drawing. This process deposits a phosphating film with a thickness of 3-10 μm on the surface of the wire rod, reducing friction and preventing surface scratches.
[0018] Furthermore, in step four, the drawing deformation is 8-15%, the drawing rate is ≤2.5m / s, and the number of drawing repetitions is 9-12.
[0019] Furthermore, in step four, the tempered martensitic steel wire has a lamellar structure with a thickness of 15~20 nm.
[0020] The 3000MPa grade ultra-high strength steel wire obtained by the above preparation method has a wire diameter of 4.9~5.5 mm, a tensile strength of 2980~3050MPa, and a microstructure of tempered martensite. Its strength under the same strain is increased by 500~600MPa compared to traditional pearlitic steel wire.
[0021] Preparation Principle: This invention utilizes a medium-to-high carbon (0.6~0.8 wt% C) composition combined with a process path of "austenitic quenching → short-time medium-temperature tempering → large-strain multi-pass cold drawing → medium-temperature aging strengthening." Its microstructure evolution differs fundamentally from the conventional coherent deformation of "ferrite + pearlite." Instead, it achieves an ultrafine nanosheet tempered martensite matrix and overcomes the traditional bottleneck of strength-toughness antagonism by leveraging the chemical metastableness and synergistic diffusion behavior of multiple elements before and after deformation. The microalloying synergistic mechanism of this invention is detailed below:
[0022] (1) Carbon: As the most common strengthening element in carbon steel, medium to high carbon content provides a sufficient interstitial solid solution atomic source. During early quenching, it ensures the initial hardness of the full martensitic matrix. During tempering and final aging, it continuously supplies the construction of lamellar carbides (30 nm) and ultrafine dispersed carbides (3 nm) as the main solute element. The mass percentage of C is controlled at 0.6%~0.8%.
[0023] (2) Manganese and Chromium: During the austenitization process in step one and the subsequent quenching, Mn and Cr exhibited a strong synergistic effect in regulating the non-equilibrium phase transformation. The synergistic solid solution of Mn and Cr significantly reduced the martensite initiation temperature (Mn). s ) and end temperature (M f Driven by extremely high supercooling shear, the newly formed martensitic laths and substructure are refined to an extreme degree. Furthermore, the micro-regional segregation of Cr atoms at the austenite grain boundaries, combined with the rapid quenching process, strongly suppresses any thermally activated coarsening tendency of the austenite grains before quenching. This results in the final all-martensitic wire rod possessing extremely fine, spatially fragmented martensitic lath bundles, thus mitigating the early brittle fracture risk caused by coarse acicular structures in high-hardness martensite from the outset.
[0024] (3) Silicon and Chromium: During step two, supersaturated carbon undergoes non-equilibrium precipitation in the quenched martensite. At this time, Si and Cr form a dual thermodynamic and kinetic barrier against microstructure coarsening. Si has extremely low solid solubility in cementite (Fe3C). When lamellar carbides begin to precipitate between the martensite laths, a high concentration of Si atom repulsion segregation layer is instantly established in the ferrite matrix at the precipitation front. Since Si is difficult to push into the cementite lattice, this segregation layer becomes a barrier that prevents carbon atoms from continuing to diffuse laterally into the cementite, forcing the carbide lamellars to grow only longitudinally along the lath boundaries and unable to coarsen laterally. This successfully locks in an ultrafine layered tempered martensite microstructure with a phase spacing of only about 30 nm. At the same time, some Cr dissolves into the precipitated carbides, forming (Fe, Cr)3C type composite carbides. Since the diffusion rate of Cr atoms at 400~450 ℃ is much lower than that of carbon atoms, its presence greatly reduces the interfacial mobility of carbides. Kinetically, it works in synergy with Si to ensure that carbides can fully nucleate during short tempering time without undergoing Ostwald ripening.
[0025] (4) Silicon and Manganese: In step S5, the 30 nm lamellar tempered martensite undergoes intense tensile strain. Si and Mn synergistically regulate the rheological stress and phase stability of the matrix at this stage. The high Si content strongly dissolves in the ferrite matrix, significantly improving the lattice distortion and shear resistance of the matrix. Under intense cold drawing strain, the high concentration of dissolved Si forces multi-system slip within the lamellar ferrite, activating high-density dislocation cells and subgrain boundary movements, preventing localization of plastic deformation. As the true strain reaches 1.90, the lamellar thickness is forcibly reduced to 15 nm. Under extremely high mechanical shear force, the Mn atoms dissolved in the matrix become carbide-forming elements, altering the carbon chemical potential on both sides of the interface. This stress field generated by strain, combined with Mn-C affinity, drives some lamellar carbides to undergo local "mechanical dissolution," releasing carbon atoms that are captured in large quantities in a non-equilibrium state at high-density dislocation cores or segregated at the nanosheet interface. This dynamic process redistributes carbon atoms within the matrix, laying the groundwork for a massive number of supersaturated nucleation sites for subsequent aging precipitation.
[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0027] 1. By employing quenching and extremely short-time tempering, tempered martensite containing nano-plate carbides is obtained, which combines high strength and high plasticity, and can be drawn without breaking the wire under low strain.
[0028] 2. The formation of nanosheet crystals by pulling and the precipitation of dispersed carbides by aging achieve a triple synergy of fine grain strengthening, dislocation strengthening and second phase strengthening;
[0029] 3. The process is simple and easy to implement. The original pearlitic wire rod is transformed into tempered martensitic wire rod through quenching and short-time tempering, which reduces the isothermal transformation time. The short-time aging after drawing can reduce the heat impact of subsequent coatings, and can obtain millimeter-level 3000MPa grade steel wire under limited strain. Attached Figure Description
[0030] Figure 1 This is an engineering stress-strain curve of a 4.9mm tempered martensitic steel wire in the drawn state and after subsequent aging, as shown in Embodiment 1 of the present invention.
[0031] Figure 2 This is a comparison chart of the performance of 4.9mm tempered martensitic steel wire and pearlitic steel wire under various strains in Embodiment 1 of the present invention;
[0032] Figure 3 This is a TEM image of the 12.5mm tempered martensitic steel wire rod of the present invention;
[0033] Figure 4 These are the TEM bright-field images and corresponding dark-field images of the 4.9mm tempered martensitic steel wire after drawing and aging according to the present invention, where a is the TEM bright-field image and b is the TEM dark-field image. Detailed Implementation
[0034] Unless otherwise specified, all materials and reagents used in the following embodiments are commercially available. Experimental methods not specifically described in the embodiments are generally performed under standard conditions or as recommended by the manufacturer.
[0035] Example 1
[0036] A method for preparing 3000MPa grade ultra-high strength steel wire includes the following steps:
[0037] S1. Material Selection: Medium carbon low alloy wire rod is used, with the following mass percentages: C: 0.6 wt%, Mn: 0.5 wt%, Si: 0.5 wt%, Cr: 0.3 wt%, and the balance being Fe.
[0038] S2. Austenitization and quenching: The wire rod is heated to 860 ℃ and held for 8 min to austenitize, and then quenched to obtain a fully martensitic wire rod.
[0039] S3. Short-time medium-temperature tempering: Tempering at 400 ℃ for 20 s causes the precipitation of lamellar carbides with a spacing of about 35 nm between the martensitic laths, resulting in tempered martensitic wire rods with high strength and high plasticity.
[0040] S4. Surface pretreatment: The heat-treated tempered martensitic wire rod is repeatedly bent and peeled by high-speed shot blasting to remove the oxide film, and then subjected to surface phosphating lubrication protection treatment, that is, immersion treatment in 80°C manganese-based phosphating solution to deposit a phosphating film with a thickness of 5 μm on the wire rod surface, reducing friction and preventing surface scratches.
[0041] S5. Multi-pass immersion drawing: The phosphated wire rod is subjected to multi-pass immersion drawing deformation in a water tank. The cold drawing process is repeated until the true strain ε≥1.90, and the wire rod is drawn to a diameter of 4.9 mm with a deformation of 8% at a drawing rate of 2.0 m / s. This yields a tempered martensitic wire rod with a lamellar thickness of 20 nm and a diameter of 12.5 mm. The repeated cold drawing consists of 9 consecutive passes.
[0042] S6, Medium-temperature aging strengthening: After drawing, the wire rod is held at 350 ℃ for 10 min, and then immediately cooled with water mist. 3nm ultrafine carbides are dispersed and precipitated at the nanosheet interface to obtain ultra-high strength medium-high carbon tempered martensitic steel wire.
[0043] The high-strength steel wire produced was subjected to performance tests, and the engineering stress-strain curve of the tempered martensitic steel wire was obtained by referring to... Figure 1 It can be seen that the ultimate strength of the steel wire in the drawn state (true strain ε=1.90) is 2780 MPa, and the strength of the steel wire after annealing at 350 ℃ for 10 min increases by 240 MPa. Figure 2 As can be seen, compared with pearlitic steel wire produced by traditional processes, carbon steel wire rod of the same composition, under the same drawing strain, has a tensile strength of approximately 3020 MPa, which is about 20% higher, and the tensile strength increases by about 500 MPa. There is no significant difference in the maximum elongation at break (2.5%) and the maximum number of torsion turns (10 turns). The microstructure of the steel wire obtained in this embodiment is tempered martensite.
[0044] like Figure 3 As shown, after quenching and short-time medium-temperature tempering, the original wire rod exhibits typical tempered martensitic microstructure characteristics. A martensitic lath bundle structure is clearly visible, with fine and dispersed lamellar carbides distributed between the laths. The precipitation of these nanoscale carbides effectively strengthens the matrix and provides excellent plasticity reserves for subsequent cold drawing processes, ensuring drawability under low strain.
[0045] like Figure 4As shown, after low-strain cold drawing, the original martensitic laths underwent severe plastic deformation along the drawing direction, evolving into a nanoscale layered structure with a thickness of approximately 20 nm, forming tempered martensitic wire rods. Simultaneously, the areas marked in the dark-field image confirm that during the aging process after drawing, ultrafine carbides with a size of approximately 3 nm were successfully dispersed and precipitated at the nanosheet interfaces. This dual microstructure of nanosheet crystals and dispersed ultrafine carbides achieves a synergistic effect of fine-grain strengthening, dislocation strengthening, and second-phase strengthening, thereby enabling the steel wire to achieve an ultra-high strength of 3000 MPa at a diameter in the millimeter range.
[0046] Example 2
[0047] A method for preparing 3000MPa grade ultra-high strength steel wire includes the following steps:
[0048] S1. Material Selection: High-carbon low-alloy wire rod is used, with the following mass percentages: C: 0.7 wt%, Mn: 0.8 wt%, Si: 1.0 wt%, Cr: 0.4 wt%, and the balance being Fe.
[0049] S2. Austenitization and quenching: Heat the wire rod to 860 ℃ and hold for 15 min to austenitize it, then quench it to obtain a fully martensitic wire rod.
[0050] S3. Short-time medium-temperature tempering: Tempering at 420 ℃ for 20 s causes the precipitation of lamellar carbides with a spacing of about 35 nm between the martensitic laths, resulting in tempered martensitic wire rods with high strength and high plasticity.
[0051] S4. Surface pretreatment: The heat-treated tempered martensitic wire rod is repeatedly bent and peeled by high-speed shot blasting to remove the oxide film, and then subjected to surface phosphating lubrication and protection treatment, namely, immersion treatment in 85°C manganese-based phosphating solution, to deposit a phosphating film with a thickness of 6 μm on the wire rod surface, reducing friction and preventing surface scratches.
[0052] S5. Multi-pass immersion drawing: The phosphated wire rod is subjected to multi-pass immersion drawing deformation in a water tank. The cold drawing process is repeated until the true strain ε≥1.90, and the wire rod is drawn to a diameter of 5.1 mm with a deformation of 12% at a drawing rate of 2.2 m / s. This yields a tempered martensitic wire rod with a lamellar thickness of 20 nm and a diameter of 12.5 mm. The repeated cold drawing consists of 11 consecutive passes.
[0053] S6, Medium-temperature aging strengthening: After drawing, the wire rod is held at 350 ℃ for 15 min, and then immediately cooled with water mist. 3nm ultrafine carbides are dispersed and precipitated at the nanosheet interface to obtain ultra-high strength medium-high carbon tempered martensitic steel wire.
[0054] The high-strength steel wire produced was subjected to performance tests, and its tensile strength was approximately 2980 MPa. Compared to pearlitic steel wire produced using conventional processes, which has a tensile strength of approximately 2400 MPa, the tensile strength increased by approximately 480 MPa. The wire achieved a maximum elongation at break of 2.9% and a maximum number of torsion turns of 13, with no significant difference. The microstructure of the steel wire obtained in this embodiment is tempered martensite.
[0055] Example 3
[0056] A method for preparing 3000MPa grade ultra-high strength steel wire includes the following steps:
[0057] S1. Material Selection: High-carbon low-alloy wire rod is used, with the following mass percentages: C: 0.8 wt%, Mn: 1.0 wt%, Si: 1.5 wt%, Cr: 0.6 wt%, and the balance being Fe.
[0058] S2. Austenitization and quenching: Heat the wire rod to 860 ℃ and hold for 12 min to austenitize it, then quench it to obtain a fully martensitic wire rod.
[0059] S3. Short-time medium-temperature tempering: Tempering at 450 ℃ for 60 s causes the precipitation of lamellar carbides with a spacing of about 35 nm between the martensitic laths, resulting in tempered martensitic wire rods with high strength and high plasticity.
[0060] S4. Surface pretreatment: The heat-treated tempered martensitic wire rod is repeatedly bent and peeled by high-speed shot blasting to remove the oxide film, and then subjected to surface phosphating lubrication and protection treatment, namely, immersion in 90°C manganese-based phosphating solution to deposit a phosphating film with a thickness of 8 μm on the wire rod surface, reducing friction and preventing surface scratches.
[0061] S5. Multi-pass immersion drawing: The phosphated wire rod is subjected to multi-pass immersion drawing deformation in a water tank. The cold drawing process is repeated until the true strain ε≥1.90, and the wire rod is drawn to a diameter of 5.5 mm with a deformation of 15% at a drawing rate of 2.5 m / s. This yields a tempered martensitic wire rod with a lamellar thickness of 20 nm and a diameter of 12.5 mm. The repeated cold drawing consists of 12 consecutive passes.
[0062] S6, Medium-temperature aging strengthening: After drawing, the wire rod is held at 400 ℃ for 20 min, and then immediately cooled with water mist. 3nm ultrafine carbides are dispersed and precipitated at the nanosheet interface to obtain ultra-high strength medium-high carbon tempered martensitic steel wire.
[0063] The high-strength steel wire produced was subjected to performance tests, and its tensile strength was approximately 3000 MPa. Compared to pearlitic steel wire produced using conventional processes, which has a tensile strength of approximately 2400 MPa, the tensile strength increased by approximately 480 MPa. The wire achieved a maximum elongation at break of 2.6% and a maximum number of torsion turns of 13, with no significant difference. The microstructure of the steel wire obtained in this embodiment is tempered martensite.
[0064] Example 4
[0065] A method for preparing 3000MPa grade ultra-high strength steel wire includes the following steps:
[0066] S1. Material selection: Medium-high carbon low alloy wire rod is used, with the following mass percentages: C: 0.7 wt%, Mn: 0.7 wt%, Si: 1.2 wt%, Cr: 0.5 wt%, and the balance being Fe.
[0067] S2. Austenitization and quenching: Heat the wire rod to 850 ℃ and hold for 10 min to austenitize it, then quench it to obtain a fully martensitic wire rod.
[0068] S3. Short-time medium-temperature tempering: Tempering at 400 ℃ for 40 s causes the precipitation of lamellar carbides with a spacing of about 30 nm between the martensitic laths, resulting in tempered martensitic wire rods with high strength and high plasticity.
[0069] S4. Surface pretreatment: The heat-treated tempered martensitic wire rod is repeatedly bent and peeled to remove the oxide film by high-speed brushing, and then subjected to surface phosphating lubrication and protection treatment, namely, immersion in 80°C manganese-based phosphating solution to deposit a phosphating film with a thickness of 7 μm on the wire rod surface, reducing friction and preventing surface scratches.
[0070] S5. Multi-pass immersion drawing: The phosphated wire rod is subjected to multi-pass immersion drawing deformation in a water tank. The cold drawing process is repeated until the true strain ε≥1.90, and the wire rod is drawn to a diameter of 5.3 mm with a deformation of 10% and a drawing rate ≤2.3 m / s. This yields a tempered martensitic wire rod with a lamellar thickness of 17 nm and a wire rod diameter of 12.5 mm. The repeated cold drawing consists of 11 consecutive drawing passes.
[0071] S6, Medium-temperature aging strengthening: After drawing, the wire rod is held at 300 ℃ for 18 min, and then immediately cooled with water mist. 3 nm ultrafine carbides are dispersed and precipitated at the nanosheet interface to obtain ultra-high strength medium-high carbon tempered martensitic steel wire.
[0072] The tensile strength of the steel wire obtained in this embodiment is 3010 MPa, and the microstructure is tempered martensite.
[0073] Example 5
[0074] A method for preparing 3000MPa grade ultra-high strength steel wire includes the following steps:
[0075] S1. Material Selection: Medium-high carbon low alloy wire rod is used, with the following mass percentages: C: 0.67 wt%, Mn: 0.65 wt%, Si: 1.35 wt%, Cr: 0.55 wt%, and the balance being Fe.
[0076] S2. Austenitization and quenching: The wire rod is heated to 860 ℃ and held for 8 min to austenitize, and then quenched to obtain a fully martensitic wire rod.
[0077] S3. Short-time medium-temperature tempering: Tempering is performed at 400~450 ℃ for 20~60 s to precipitate lamellar carbides with a spacing of about 30~35 nm between the martensite laths, thereby obtaining tempered martensite wire rods with high strength and high plasticity.
[0078] S4. Surface pretreatment: The heat-treated tempered martensitic wire rod is repeatedly bent and peeled to remove the oxide film by high-speed brushing, and then subjected to surface phosphating lubrication and protection treatment, namely, immersion in 85°C manganese-based phosphating solution to deposit a phosphating film with a thickness of 9 μm on the wire rod surface, reducing friction and preventing surface scratches.
[0079] S5. Multi-pass immersion drawing: The phosphated wire rod is subjected to multi-pass immersion drawing deformation in a water tank. The cold drawing process is repeated until the true strain ε≥1.90, and the wire rod is drawn to a diameter of 5.3 mm with a deformation of 13.5% and a drawing rate ≤2.1 m / s, to obtain a tempered martensitic wire rod with a lamellar thickness of 15 nm and a wire rod diameter of 13 mm. The repeated cold drawing consists of 11 consecutive drawing passes.
[0080] S6, Medium-temperature aging strengthening: After drawing, the wire rod is held at 400 ℃ for 10 min, and then immediately cooled with water mist. 3 nm ultrafine carbides are dispersed and precipitated at the nanosheet interface to obtain ultra-high strength medium-high carbon tempered martensitic steel wire.
[0081] The tensile strength of the steel wire obtained in this embodiment is 3080 MPa, and the microstructure is tempered martensite.
[0082] Of the above embodiments, the preferred embodiment is Embodiment 5.
[0083] Comparative Example 1
[0084] The remaining steps of this comparative example are the same as those in Example 5, except that the heating temperature in step S2 is replaced with 800 ℃ and the holding time is replaced with 2 min. The results showed that the wire rod was not completely austenitized, and coarse ferrite structure existed after cooling.
[0085] Comparative Example 2
[0086] The remaining steps of this comparative example are the same as those in Example 5, except that the heating temperature in step S2 is replaced with 900 ℃ and the holding time is replaced with 20 min. The results showed that severe decarburization occurred in the wire rod, with a decarburized layer thickness exceeding 0.1 mm.
[0087] Comparative Example 3
[0088] The remaining steps in this comparative example are the same as in Example 5, except that the tempering time in step S3 is replaced with 8 seconds. The results showed that insufficient tempering time for the quenched martensitic wire rod resulted in poor plasticity recovery, increased wire breakage rate during subsequent drawing, and difficulty in drawing.
[0089] Comparative Example 4
[0090] The remaining steps in this comparative example are the same as in Example 5, except that the tempering time in step S3 is replaced with 100 s. The results showed that excessively long tempering time for the quenched martensitic wire rod led to sufficient dislocation recovery, resulting in a decrease in the strength of the tempered martensitic wire rod.
[0091] Comparative Example 5
[0092] The remaining steps of this comparative example are the same as those in Example 5, except that the tempering temperature in step S3 is replaced with 500°C. The results showed that carbides spheroidized, the interlamellar spacing of the tempered martensitic steel wires increased, and the strength decreased significantly.
[0093] Comparative Example 6
[0094] A method for preparing steel wire includes the following steps:
[0095] High-carbon, low-alloy wire rods were used, with the following mass percentages: C: 0.82 wt%, Mn: 0.55 wt%, Si: 1.2 wt%, Cr: 0.5 wt%, and the balance being Fe. The rods were heated to 860 ℃ and held for 10 min for austenitization, followed by isothermal treatment in a 580 ℃ salt bath to obtain sorbitic wire rods. The phosphated wire rods were then subjected to multiple passes of immersion drawing in a water bath, with repeated cold drawing processes until the true strain ε=2.0 was achieved. The rods were drawn to a diameter of 5.5 mm, with a deformation of 12% and a drawing rate ≤2.3 m / s, yielding tempered martensitic wire rods with a lamellar thickness of 17 nm and a diameter of 12.5 mm. The repeated cold drawing consisted of 11 consecutive passes. The results showed that the prepared steel wire had a tensile strength of 2350 MPa, a maximum elongation of 2.7%, and a maximum torsion count of 15 turns.
[0096] Performance Comparison
[0097] Table 1. Comparison of the microstructure and properties of steel wire obtained from different wire rod compositions and preparation methods.
[0098]
[0099] As shown in Table 1, Examples 1-5, quenching and short-term medium-temperature tempering can make the non-deformable martensitic structure drawable. The tempered martensitic steel wire prepared by multi-pass drawing has an approximately 20% performance improvement compared to pearlitic steel wire prepared by known processes. Further medium-temperature aging treatment improves the strength-plasticity matching and torsional properties, and the final product has a strength grade of 3000 MPa, a uniform elongation of ≥2.5, and a torsion count of ≥10.
Claims
1. A method for preparing 3000MPa grade ultra-high strength steel wire, characterized in that, Includes the following steps: Step 1: Heat the medium-high carbon low alloy wire rod to austenitize it, and then quench it to obtain quenched martensitic wire rod. Step 2: Temper at 400~450 ℃ to obtain wire rod with tempered martensite structure; Step 3: Remove the oxide film from the wire rod with tempered martensite structure and perform phosphating lubrication protection treatment; Step 4: Perform multiple immersion water tank drawing processes on the material obtained in Step 3, controlling the true strain of cold drawing ε≥1.90, to obtain tempered martensitic steel wire. Step 5: Hold the material obtained in Step 4 at 300~400 ℃ for 10~20 min, then immediately cool it with water mist to obtain 3000MPa grade ultra-high strength steel wire; In step one, the medium-high carbon low alloy wire rod comprises the following elements by mass percentage: C: 0.6~0.8 wt%, Mn: 0.5~1.0 wt%, Si: 0.5~1.5 wt%, Cr: 0.3~0.6 wt%, with the balance being Fe; In step two, the tempering time is 20~60 s.
2. The method for preparing 3000MPa grade ultra-high strength steel wire according to claim 1, characterized in that: In step one, the heating temperature is 850~860 ℃, and the temperature is maintained for 8~15 min.
3. The method for preparing 3000MPa grade ultra-high strength steel wire according to claim 1, characterized in that: In step two, plate-like carbides with a spacing of 30-35 nm precipitate from the wire rod with tempered martensite structure.
4. The method for preparing a 3000MPa grade ultra-high strength steel wire according to claim 1, characterized in that: In step three, the oxide film is removed by acid washing or mechanical methods.
5. The method for preparing a 3000MPa grade ultra-high strength steel wire according to claim 1, characterized in that: In step three, the phosphating lubrication protection treatment involves immersing the wire rod with tempered martensitic structure in a zinc-based or manganese-based phosphating solution at 80-90°C before drawing, and depositing a phosphating film with a thickness of 3-10 μm on the surface of the wire rod.
6. The method for preparing a 3000MPa grade ultra-high strength steel wire according to claim 1, characterized in that: In step four, the drawing deformation is 8-15%, the drawing rate is ≤2.5m / s, and the number of drawing repetitions is 9-12.
7. The method for preparing 3000MPa grade ultra-high strength steel wire according to claim 1, characterized in that: In step four, the tempered martensitic steel wire has a lamellar structure with a thickness of 15~20 nm.
8. A 3000MPa grade ultra-high strength steel wire obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The steel wire has a diameter of 4.9~5.5 mm, a tensile strength of 2980~3050 MPa, and a microstructure of tempered martensite.
Citation Information
Patent Citations
Processing method of high-speed steel wire
CN113430361A
Production method of high-strength low-residual-stress spring steel wire
CN117265248A